Pembinaan Manajemen Madrasah Berbasis Akhlakul Karimah bagi Kepala Madrasah dan Guru di MAN 3 Kota Jambi: Penelitian - M. Sulikah; Rafik Darmansyah; Nadiyah; Mastikawati; Kompri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program (PKM) aims to strengthen the managerial competence of madrasah leaders and teachers through the theme “Madrasah Management Development Based on Akhlakul Karimah.” The program was conducted on November 21, 2025, at MAN 3 Kota Jambi, involving 40 participants consisting of the principal, vice principals, and teachers. Using a participatory training approach, the activity integrated interactive lectures, discussions, and problem-solving sessions facilitated by Dr. Rafik Darmansyah, M.Pd.I. The purpose of this PKM was to enhance the participants’ understanding of value-based management and its application in building a religious, ethical, and effective educational environment. The results show that participants demonstrated high enthusiasm and actively engaged in discussions, reflecting a strong need for value-oriented managerial development. They gained new insights regarding leadership ethics, communication improvement, discipline strengthening, and moral-based decision-making. The training also highlighted current challenges faced by the madrasah, such as limited internal coordination and the need for systematic character-building programs. Participants reported that the practical examples provided helped them visualize the integration of akhlakul karimah into daily managerial practices. The activity concluded with recommendations for follow-up trainings focusing on program planning, academic supervision, and value-based leadership. Overall, this PKM contributed significantly to enhancing the managerial capacity and moral awareness of educators at MAN 3 Kota Jambi, supporting the development of a harmonious and quality-oriented madrasah environment.